Thermal sensitivity of feeding and burrowing activity of an invasive crayfish in UK waters. Issue 1 (27th October 2020) - Rodríguez Valido, César A.; Johnson, Matthew F.; Dugdale, Stephen J.; Cutts, Vanessa; Fell, Henry G.; Higgins, Emma A.; Tarr, Simon; Templey, Clare M.; Algar, Adam C.
Abstract: Climate change and invasive species are among the biggest threats to global biodiversity and ecosystem function. Although the individual impacts of climate change and invasive species are commonly assessed, we know far less about how a changing climate may impact invading species. Increases in water temperature due to climate change are likely to alter the thermal regime of UK rivers, and this in turn may influence the performance of invasive species such as signal crayfish ( Pacifastacus leniusculus ), which are known to have deleterious impacts on native ecosystems. We evaluate the relationship between water temperature and two key performance traits in signal crayfish—feeding and burrowing rate—using thermal experiments on wild‐caught individuals in a laboratory environment. Although water temperature was found to have no significant influence on burrowing rate, it did have a strong effect on feeding rate. Using the thermal performance curve for feeding rate, we evaluate how the thermal suitability of three UK rivers for signal crayfish may change as a result of future warming. We find that warming rivers may increase the amount of time that signal crayfish can achieve high feeding rate levels. These results suggest that elevated river water temperatures as a result of climate change may promote higher signal crayfish performance in the future, further exacerbating the ecological impact of this invasive species.